(untitled) (Al-Academy, 2024)
Logos, in their formal form, represent an identification card and identity for the institution to which they are affiliated. They are their visual means of communicating and communicating with the recipient. Therefore, the emphasis of these institutions was on creating an ideal design for this identity in a simplified form that directly reflects the idea to the recipient. Thus, many international logo designs went through stages of Transformation until it reached the adoption of a visual form of written text only. This is what the current research represents from a study that adopted the analytical method for a number of international slogans that underwent these textual transformations. The research problem was represented in the following question (what is the importance of the visual-textual transformation in the design of international slogans, and its job role)? The goal of the research was set at (identifying the visual-textual transformations of international logos and their role in achieving the desired functional goal). The research covered topics such as the direct impact of these transformations, the identity and mental image of logo design, and appearance simplification. In addition to the functional goal of textual logos and ways to achieve it. The research came out with a set of results. The most prominent of which are: - The style of modernity and the influences of art schools were prominently achieved in the textual transformations that occurred in the design of international logos. Likewise, the textual transformations in the design of logos created visually distinct trademarks